THE INFLUENCE OF LEADERSHIP, ORGANIZATIONAL CULTURE, MOTIVATION AND COMPENSATION ON EMPLOYEE PERFORMANCE IN REGIONAL APPARATUS ORGANIZATIONS (OPD) AT BAPERLITBANG KARIMUN REGENCY - Wira Herlambang; Indrayani Indrayani; Muammar Khaddafi (RADJA PUBLIKA, 2022)
Performance is the result of work achieved a person or group of people by a company or organization according to their respective authorities and responsibilities in an effort to achieve the goals of the company or organization. The existence oforganization the regional apparatus Baperlitabang Karimun Regency has an important role in the effort to accelerate the socialization and development of regional development, especially in Regency Karimun. Karimun Regency Baperlitbang is inseparable from the role of human resources who have provided their manpower, talents, creativity, and efforts to the organization. Human resources are the most important thing for determining goals organizational. Therefore every organization will always try to improve the performance of its employees in the hope that what the goals of the company or organization will be achieved.